Power system stability enhancement using static synchronous series compensator (SSSC) - Faridi, M; Maeiiat, H; Karimi, M; Farhadi, P; Mosleh, H (2011 3rd International Conference on Computer Research and Development, 2011)
In this study, a static synchronous series compensator (SSSC) is used to investigate the effect of this device in controlling active and reactive powers as well as damping power system oscillations in transient mode. The SSSC equipped with a source of energy in the DC link can supply or absorb the reactive and active power to or from the line. Simulations have been done in MATLAB/SIMULINK environment. Simulation results obtained for selected bus-2 in two machine power system shows the efficacy of this compensator as one of the FACTS devices member in controlling power flows, achieving the desired value for active and reactive powers, and damping oscillations appropriately.